2009
DOI: 10.4049/jimmunol.0902878
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: HLA-DM–Mediated Peptide Exchange Functions Normally on MHC Class II–Peptide Complexes That Have Been Weakened by Elimination of a Conserved Hydrogen Bond

Abstract: The mechanism by which HLA-DM (DM) promotes exchange of peptides bound to HLA-DR (DR) is still unclear. We have shown that peptide interaction with DR1 can be considered a folding process as evidenced by cooperativity. However, in DM-mediated ligand exchange, prebound peptide release is noncooperative, which could be a function of the breaking of a critical interaction. The hydrogen bond (H-bond) between β-chain His81 and the peptide backbone at the −1 position is a candidate for such a target. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 11 publications
2
39
1
Order By: Relevance
“…Because the immunogenicity of epitopes after infection and vaccination is strongly linked to their relative DM susceptibility (8,13,58,59), understanding these determinants is crucial to follow immune responses, improve vaccines, and understand the etiology of autoimmune disease. Previous models for predicting DM susceptibility have variously implicated particular conserved hydrogen bonds near pocket 1 (17,18,20,21), spontaneous dissociation of the peptide N terminus (22,60), conformational lability of the 3 10 helical region adjacent to pocket 1 (23), an SDS-sensitive flexible conformation determined by pocket 1 occupancy (28,45), and an "compare-exchange-pushoff" mechanism (25). Although these different approaches have generally implicated interactions around the pocket 1 region (61), some studies are consistent with more distributed effects (16,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the immunogenicity of epitopes after infection and vaccination is strongly linked to their relative DM susceptibility (8,13,58,59), understanding these determinants is crucial to follow immune responses, improve vaccines, and understand the etiology of autoimmune disease. Previous models for predicting DM susceptibility have variously implicated particular conserved hydrogen bonds near pocket 1 (17,18,20,21), spontaneous dissociation of the peptide N terminus (22,60), conformational lability of the 3 10 helical region adjacent to pocket 1 (23), an SDS-sensitive flexible conformation determined by pocket 1 occupancy (28,45), and an "compare-exchange-pushoff" mechanism (25). Although these different approaches have generally implicated interactions around the pocket 1 region (61), some studies are consistent with more distributed effects (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed that DM targets the conserved hydrogen bonds between MHCII and peptide in the vicinity of the P1 pocket (17,18), although others found that these interactions are dispensable for DM action (20,21,23,27). Peptide side chain pocket interactions also have been implicated in DM susceptibility, particularly emphasizing the importance of pocket 1 near the N terminus of the bound peptide (22,28).…”
Section: Antigen Presentation To Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which DM mediates these effects has received much attention (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Peptides are released by DM with different rates (18), with DM susceptibility a major factor in whether or not a particular peptide is recognized by the cellular immune system (19)(20)(21).…”
mentioning
confidence: 99%
“…Although the precise mechanism by which DM effects peptide exchange on MHC-II remains controversial (81)(82)(83)(84)(85)(86)(87), recent evidence suggests that the ability of MHC-II to interact with DM is driven by a conformational change in the region of the MHC-II α chain 3 10 helix (88). In this regard, tapasin and DM may both function as chaperones that give MHC-I and MHC-II molecules, respectively, a chance to fold around tightly binding antigenic peptides needed for molecular stability and effective immune function.…”
Section: Discussionmentioning
confidence: 99%